Color Doppler sonography of the aortic isthmus in intrauterine growth-restricted fetuses and normal fetuses - Ladan Younesi; Mostafa Ghadamzadeh; Zeinab Safarpour Lima; Ghazaleh Amjad (PAGEPress Publications, 2018)
Intrauterine growth restriction is associated with a significant increase in morbidity and perinatal mortality, and increases the likelihood of fetal death, asphyxia, meconium aspiration, hypoglycemia, and neonatal hypothermia. The aim of this study was to determine aortic isthmus flow difference by using color doppler sonography in Intrauterine growth restriction and normal fetuses. The data presented were obtained from 30 mothers, who referred to the radiology department of Akbarabadi Hospital of Tehran with a diagnosis of intrauterine growth restriction. An ultrasound was performed to determine the status of placenta, fetus, and amniotic fluid. The umbilical arterial doppler assessment was used to confirm diagnosis of intrauterine growth restriction. Thirteen (43.3%) were nulliparous mothers and 17 (56.7%) were multiparous mothers. 30 pregnant women with healthy fetuses were enrolled as control group. According to the ultrasound findings, Dactus Venus wave type was recorded in intrauterine growth restriction fetuses, which was reported as normal (26 subjects; 86.7%) and abnormal (4 subjects; 13.3%). All together, this study provides appropriate guidance to use doppler for delivery timing and to control risk factors.